The 3D Bioprinted Scaffolds for Wound Healing - Antezana, Pablo Edmundo (2022)
Skin tissue engineering and regeneration aim at repairing defective skin injuries and progress in wound healing. Until now, even though several developments are made in this field, it is still challenging to face the complexity of the tissue with current methods of fabrication. In this review, short, state-of-the-art on developments made in skin tissue engineering using 3D bioprinting as a new tool are described. The current bioprinting methods and a summary of bioink formulations, parameters, and properties are discussed. Finally, a representative number of examples and advances made in the field together with limitations and future needs are provided.